Concentrated Growth Factors Combined with Lipopolysaccharide Stimulate the In Vitro Regenerative and Osteogenic Activities of Human Dental Pulp Stem Cells by Balancing Inflammation - Negin Firouzi; Hamid Reza Yavari; Saeed Rahimi; Leila Roshangar; Ramtin Chitsazha; Mohammad Amini (International Journal of Dentistry)
Aim. We investigated the long-term effects of exposure to concentrated growth factors (CGFs) on the regenerative properties of dental pulp stem cells (DPSCs) in the presence and absence of lipopolysaccharide (LPS) as a proinflammatory agent. Methods. DPSCs were cultured with CGF at different concentrations of LPS (0.1, 1, and 10 µg/ml) for 21 days. Then, using MTT and scratch assays, the cell viability and migration were examined. Osteogenic stimulation was evaluated by alkaline phosphatase (ALP) staining and Sirius Red staining, which determined the ALP activity and collagen levels, respectively. The expression levels of osteogenic markers were quantified using the qRT-PCR method. One-way analysis of variance (ANOVA) and Tukey’s HSD test were used to analyze differences between groups. Results. Long-term treatment of DPSCs with CGFs reduced LPS-induced cell death. Moreover, CGF and LPS (1 µg/ml), either in combination or alone, improved the DPSC migratory ability and caused a significant increase in osteogenic stimulation through the upregulation of collagen levels and ALP activity. Additionally, CGFs significantly upregulated RUNX2, DSPP, OCN, and OPN mRNA levels (as osteogenic markers), while LPS (1 µg/ml) only significantly increased OCN overexpression. Conclusion. Our findings are evidence that CGF could be a promising agent to induce dentin-pulp complex healing in long-term chronic inflammation.